Kempong, A Traditional Fermented Food in Karangpucung Kidul village, Linggapura Bumiayu, Central Java: Fermentation Agent and Their Roles - Isworo Rukmi; Devia Kusmawati Arfina; Endang Kusdiyantini (Indonesian Association of Food Technologists, 2017)
Kempong is a traditional fermented food that is found only in South Karangpucung Linggapura Bumiayu village, Central Java. It is prepared from palm kernel cake (PKC). This fermented food is consumed mostly everyday by the people in the village as a side dish or snack. Study on the mold important in the kempong fermentation was done by isolating molds from kempong, PKC, laru and the air of preparation room. Eleven species of molds were successfully isolated from different samples. Among the mold isolates three species came out from kempong product, i.e. R. oryzae, E. chevaliery and A. oryzae. The isolates showed the capability in producing amylase, protease, lipase, and cellulase. Both R. oryzae and A. oryzae indicated as the main fermentation mold in kempong production, because the inoculum laru only contained these two species.